Optimization for high-level expression in pichia pastoris and purification of truncated and full length recombinant SAG2 of toxoplasma gondii for diagnostic use - Ling, L.Y.; Ithoi, Init; Fong, Mun Yik (SEAMEO Regional Tropical Medicine and Public Health Network, 2010)
SAG2 is one of the major surface antigens of the intracellular protozoan parasite Toxoplasma gondii. In the present study, truncated recombinant SAG2(S) and full length recombinant SAG2(T) of T. gondii were optimally produced (similar to 15 mg/liter) in Pichia pus tons expression system using BMMY medium at pH 3, 25 degrees C in 0.5-1 methanol and a time-course of 1-2 days. The recombinant proteins were purified using a commercial gel filtration purification system obtaining similar to 33 recovery. The purified SAG2(S) and SAG2(T) showed molecular masses of 45 and 36 kDa by SDS-PAGE, respectively. The recombinant proteins were evaluated by Western blotting with patients' sera and demonstrated 90 sensitivity and 100 specificity for detection of toxoplasmosis. This study provided a means for large-scale expression and purification of SAG2, which should be useful for diagnosis of toxoplasmosis.